A poetics of Third Theatre : performer training, dramaturgy, cultural action - Turner, Jane; Campbell, Patrick (New York: Routledge, 2021)
"A Poetics of Third Theatre offers an in-depth, critical analysis of Third Theatre, a transnational community of theatre groups and artists united by a shared set of values and a laboratory attitude. This book takes a genealogical account of Third Theatre as a concept and a practice that draws attention to the historical Third Theatre Encounters which have taken place across Europe and Latin America since the 1970s. The work of renowned Third Theatre groups and organisations, such as LUME (Brazil), Grupo Cultural Yuyachkani (Peru), Triangle Theatre (UK) and Nordisk Teaterlaboratorium - NTL (Denmark), are explored to reveal how a multifarious poetics of Third Theatre is manifest through these artists' approaches to performer training, dramaturgy and cultural action. Three critical pillars - unconditional hospitality, artisanal craft and (re)enchantment - are employed in order to illuminate the shared ethos of the Third Theatre community and its exemplification as a mode of cultural performance. This informative text will be of great use to students and scholars of Drama and Theatre Studies, and its dedicated section on performer training exercises offers the reader pathways into an experiential engagement with Third Theatre craft"--
Part 1. Preface -- Third Theater: a genealogy of the concept -- Third Theater: a genealogy of the practice -- Part 2. Preface -- LUME (Brazil) -- Grupo Cultural Yuyachkani (Peru) -- Triangle Theater (UK) -- Nordisk Teaterlaboratorium: Third Theater today -- Part 3: Preface -- From interculturalism to cultural performance -- Third Theater: embodiment, craft, (re)enchantment -- Third Theater: an expanded practice -- Conclusion.
Includes bibliographical references and index.
Keywords: Experimental theater; Experimental theater